The Effectiveness of Cow Manure for Sustainable Agriculture on Purple Eggplant Plants - Erlina Rahmayuni; Jelita Almas Pramudita; Welly Herman (CV. Truly Science Publishing, 2026)
Background: Sustainable agriculture increasingly emphasizes the use of organic fertilizers to improve soil fertility and reduce environmental impact. Cow manure is widely recognized as a potential organic amendment for enhancing crop productivity. Aim: This study aimed to evaluate the effect of different doses of cow manure on the growth and yield of purple eggplant (Solanum melongena L.). Methods: A Randomized Complete Block Design was applied with five treatments of cow manure (0, 50, 75, 100, and 125 g/polybag) and five replications. Observed parameters included plant height, number of leaves, number of branches, flowering age, and yield components such as number of fruits, fruit length, fruit diameter, weight per fruit, and total fruit weight per plant. Results: The application of cow manure did not significantly affect most vegetative growth parameters. However, a dose of 100 g/polybag accelerated flowering time. Yield components such as fruit number, size, and individual fruit weight were not significantly influenced. In contrast, total fruit weight per plant showed significant differences, with the 50 g and 100 g/polybag treatments producing the highest yields (411.07 g and 409.18 g, respectively). Conclusion: Cow manure application at moderate doses (50–100 g/polybag) improves eggplant yield without significantly affecting vegetative growth. This finding supports the use of organic fertilizers as a sustainable alternative in eggplant cultivation.